Rhetorical moves of introduction sections in english linguistics research articles from two non-scopus and two scopus journals - Geng, Hui; Lee, Geok Imm; Jalaluddin, Ilyana; Tan, Helen (Academy Publication, 2023)
As the leading section in a research article (RA), the introduction typically leaves a lasting impression on the reader. It is thus necessary to make a well-crafted and organized introduction in the writing of successful RAs. However, a lack of studies has paid attention to the rhetorical moves in the non-Scopus and Scopus RA introductions in the linguistics area. Therefore, the present study first investigated the realization and essentiality of moves and steps of introductions from both corpora, and then it delved into the relationships of distributions of moves and steps of these two sources. A total of 100 English linguistics RA introductions were selected in this study. The non-Scopus and Scopus corpus each included 50 RA introductions taken from two journals. Based on the adapted Swales’ (1990) Create-A-Research-Space (CARS) model and Rasmeenin’s (2006) rationale, the analysis of the identification and essentiality of moves was conducted. The findings revealed that Move 3 Step 5 was a novel step used in both corpora. Besides, though there were no statistically significant relationships in the essentiality rate of moves and steps between the two corpora, divergence did exist in the essentiality categorization of Move 1, Move 3, Move 1 Step 3, Move 2 Step 1B and Move 3 Step 1A. The results of this study highlight the rhetorical convention and the essentiality of moves and steps in the common non-Scopus journals and the prestigious Scopus journals, providing a template for writers in constructing crafted introductions and getting them published in Scopus journals.